Mathematics-in-Industry Case Studies - Budd, Chris; Huang, Huaxiong
Mathematics-in-Industry Case Studies aims to meet the publication needs of the burgeoning community of mathematicians who work on problems that are important to industry. Its central theme is the stimulation of innovative mathematics by the modelling and analysis of such problems across the physical, biological and social sciences.